A Cross-Level Perspective on Employee Creativity: Goal Orientation, Team Learning Behavior, and Individual Creativity - Hirst, Giles; Van Knippenberg, Daan; Zhou, Jing (Academy of Management Journal, 2009)
We developed and tested a cross-level model of individual creativity, integrating goal orientation theory and team learning research. Using hierarchical linear modeling, we found cross-level interactions between individuals’ goal orientation and team learning behavior in a cross-national sample of 25 R&D teams comprising 198 employees. We hypothesized and found a nonlinear interaction between individual learning orientation and team learning behavior: in teams higher in team learning behavior, the positive relationship between learning orientation and creativity was attenuated at higher levels of learning orientation. An individual approach orientation was positively related to creativity only when team learning behavior was high.